A study on the characterisation of the species formed during fluoride removal through coagulation. (2017) - Dubery, Swati; Agarwal, Madhu; Gupta, A.B.
Various techniques for fluoride removal have been adapted like adsorption, electro (coagulation), membrane separation, Nalgonda (coagulation technique) process have been adapted to meet the fluoride standards (< 1.5 ppm). Among these, coagulation is widely applied, highly profitable and efficient technique. Here, alum is used as a coagulant leading to residual aluminium in treated water more than the permissible limit (< 0.2 ppm). In the present work, defluoridation has been observed for initial fluoride concentration of 4 ppm with reaction pH of 6.5 for optimised coagulant dose and subsequent microfiltration to meet the residual aluminium standards. As the species formed during the process play an influential role in the mechanism, the stability and size of the species in treated water has been analysed through zeta-charge and zeta-sizing. The sludge produced during the process is of environmental concern which needs proper application. Sludge was characterised through XRD, SEM, TEM analysis and it was observed that it can be applied for solidification/stabilisation.